Rural geography in Slovenia – an overview - Pelc, Stanko; Drozg, Vladimir (Journal for Geography, 2009)
The paper shows an overview of theoretical and conceptual directions in Slovene Rural Geography. The first part of the paper deals with the changes in understanding of the term rural area, and the second part discusses some theoretical concepts. The last chapter provides an overview of the most often researched topics in the field of Rural Geography in Slovenia.
Keywords: Rural Geography; theory of Geography; Slovenia